Satellite-observed strong subtropical ocean warming as an early signature of global warming - Hu Yang; Gerrit Lohmann; Christian Stepanek; Qiang Wang; Rui Xin Huang; Xiaoxu Shi; Jiping Liu; Dake Chen; Xulong Wang; Yi Zhong; Qinghua Yang; Ying Bao; et al. (Communications Earth & Environment, 2023)
Abstract Satellite observations covering the last four decades reveal an ocean warming pattern resembling the negative phase of the Pacific Decadal Oscillation. This pattern has therefore been widely interpreted as a manifestation of natural climate variability. Here, we re-examine the observed warming pattern and find that the predominant warming over the subtropical oceans, while mild warming or even cooling over the subpolar ocean, is dynamically consistent with the convergence and divergence of surface water. By comparison of observations, paleo-reconstructions, and model simulations, we propose that the observed warming pattern is likely a short-term transient response to the increased CO2 forcing, which only emerges during the early stage of anthropogenic warming. On centennial to millennial timescales, the subpolar ocean warming is expected to exceed the temporally dominant warming of the subtropical ocean. This delayed but amplified subpolar ocean warming has the potential to reshape the ocean-atmosphere circulation and threaten the stability of marine-terminating ice sheets.